KAJIAN ANALISIS PENGGUNAAN BAHASA OLEH GENERASI TUA DAN GENERASI MUDA DALAM TRADISI SYAIR ZIKIR BARAT PULAU KASU KECAMATAN BELAKANG PADANG KOTA BATAM - Fahmi; Abdul Malik; Loren, Fabio Testy Ariance; Shanty, Isnaini Leo; Irawan, Dody; Mustado, Maulida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of language styles in the tradition of West Zikir Poetry, Kasu Island, Belakang Padang District, Batam City. The reason researchers chose this object is to preserve and also analyze the use of language styles among generations contained in West Zikir Poetry. Things that are done to obtain research data using techniques, Observation, Interviews, and Documentation. Analysis techniques in this study, collecting data with Interviews, then the data is grouped and analyzed based on qualitative methods. The results of the study show that the use of language styles in West Zikir Poetry, Kasu Island, Belakang Padang District, Batam City. It was found that there were significant differences in aspects of diction, sentence structure, use of figures of speech, and orientation of communicative functions.